Vascular endothelial growth factor and oxidative damage in cancer - Ilhan, N; Ilhan, N (Pergamon-Elsevier Science Ltd, 2003)
Objectives: VEGF may be an indicator for the angiogenic potential of a tumor and stimulates NO which plays complex roles in cancer. In our study, we investigated the levels of MDA, NO and VEGF in the plasma of various types cancer patients (untreated, yet). Design and Methods: The level of VEGF was determined by using ELISA. Plasma NIDA, NO and VEGF levels were measured in 45 patients with various cancer types and in 21 healthy subjects. Results: Plasma MDA and VEGF levels were significantly higher than those of the healthy subjects (p < 0,0001). NO levels of the patients were significantly lower vs. the healthy subjects (p < 0,001). Conclusions: Increased plasma VEGF and MDA concentrations and decreased plasma NO levels have been found in patients with various types of human cancer. Howewer, the prognostic and clinical significance of plasma VEGF in cancer patients is unknown. (C) 2003 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: oxidative stress; VEGF; NO; MDA